The Relationship Of Creativity With Student Learning Outcomes In Pastry And Bakery Subjects At Smk Negeri 6 Padang - Ramadhani, Chintya Putri; Yulastri, Asmar (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research was motivated by students' low curiosity in the material being taught, resulting in low creativity and no new innovations produced by students. This occurs due to students' lack of confidence in their abilities, because they are afraid to take risks when practicing pastry and bakery. From the problems above, many students fail in pastry and bakery subjects which will have an impact on learning outcomes. The aim of this research is to describe: 1) student creativity in Pastry and Bakery subjects, 2) student learning outcomes in Pastry and bakery subjects, 3) the relationship between creativity and student learning outcomes in Pastry and bakery subjects at SMK Negeri 6 Padang . This type of research is quantitative with a correlational approach. The population in this study was class XII culinary students at SMK Negeri 6 Padang for the 2023/2024 academic year, totaling 96 people. The sample consisted of 96 people taken using a saturated sampling technique. The saturated sampling technique is that all members of the population are used as research samples. The primary data collection technique uses a questionnaire and is measured using a Likert scale. Then for secondary data using learning outcomes in the form of grades in pastry and bakery subjects. Analysis requirements test was carried out using normality tests and linearity tests, then hypothesis testing using Pearson product moment correlation analysis, and correlation significance testing with the T test using SPSS Version 21.00. The research results show that: 1) the creativity of class XII students at SMK Negeri 6 Padang is in the medium category (53.1%), 2) the learning outcomes in pastry and bakery subjects for class 4%), 3) based on hypothesis testing, there is a positive and significant relationship between creativity and student learning outcomes in the Pastry and Bakery Products subject with a significant value of 0.001.                                                                                   Keyword: Creativity, pastry and bakery learning outcomes, pastry and bakery subjects.